2008
DOI: 10.1111/j.1365-2249.2008.03698.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal damage and death in weaned mice after oral infection with Shiga toxin 2-producing Escherichia coli strains

Abstract: SummaryEnterohaemorrhagic Escherichia coli (EHEC) O157:H7 infections are considered a public health problem in both developed and developing countries because of their increasing incidence and the severity of clinical presentation. Approximately 10% of infected patients develop complications such as haemolytic uraemic syndrome (HUS) characterized by acute renal failure, thrombocytopenia and haemolytic anaemia. The precise sequence of events leading to HUS is still understood incompletely. Because of the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 46 publications
5
54
0
1
Order By: Relevance
“…We have previously shown that EHEC infection of weaned BALB/c mice can be lethal, as a consequence of systemic damage related to Stx2 toxicity (39). In addition, we have also demonstrated that renal dysfunction secondary to EHEC infection is blocked when anti-Stx2-polyclonal serum is simultaneously inoculated, confirming that Stx is responsible for renal damage and an increased plasma urea concentration (43).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…We have previously shown that EHEC infection of weaned BALB/c mice can be lethal, as a consequence of systemic damage related to Stx2 toxicity (39). In addition, we have also demonstrated that renal dysfunction secondary to EHEC infection is blocked when anti-Stx2-polyclonal serum is simultaneously inoculated, confirming that Stx is responsible for renal damage and an increased plasma urea concentration (43).…”
Section: Resultssupporting
confidence: 57%
“…The strain belonged to seropathotype A, according to the classification of Karmali et al (38). The origin, toxin type, eae variant, EHEC Hly production, and 50% cytotoxic dose in a Vero cell assay of this EHEC strain were previously characterized by Fernández-Brando et al (39).…”
Section: Methodsmentioning
confidence: 99%
“…In order to evaluate the in vivo effect of chitosan during the infection process, mice were orally challenged with a wild-type EDL933W strain, based on the model described by Brando and collaborators 9 . Another mouse group was also treated with chitosan, administered orally 2 hours post-infection, and survival was followed for one week.…”
Section: Resultsmentioning
confidence: 99%
“…The weaned mouse model is an effective and reliable animal model for studying the pathology of EHEC infection (34,43). We demonstrated that weaned mice infected with Stx2-producing E. coli O157:H7 strains, isolated from HUS patients, experience renal dysfunction and death during the 3 d postinfection.…”
Section: Protection Against Ehec Pathogenicitymentioning
confidence: 95%
“…The enterohemorrhagic Stx2-producing E. coli O157:H7 (EHEC) was isolated from a fecal specimen of a child with HUS and was characterized by Brando et al (34). Bacterial cultures were performed as previously described (34). Briefly, strains were cultured overnight at 37˚C in Tryptic Soy Broth (TSB) (Difco, Le Point de Claix, France).…”
Section: Analysis Of Ab Efficacy Against Ehec Challengementioning
confidence: 99%